A RNA producing DNA hydrogel as a platform for a high performance RNA interference system. Issue 1 (December 2018) - Song, Jaejung; Lee, Minhyuk; Kim, Taeyoung; Na, Jeongkyeong; Jung, Yebin; Jung, Gyoo; Kim, Sungjee; Park, Nokyoung
Abstract RNA interference (RNAi) is a mechanism in which small interfering RNA (siRNA) silences a target gene. Herein, we describe a DNA hydrogel capable of producing siRNA and interfering with protein expression. This RNAi-exhibiting gel (termed I-gel for interfering gel) consists of a plasmid carrying the gene transcribing siRNA against the target mRNA as part of the gel scaffold. The RNAi efficiency of the I-gel has been confirmed by green fluorescent protein (GFP) expression assay and RNA production quantification. The plasmid stability in the I-gel results in an 8-times higher transcription efficiency than that of the free plasmid. We further applied the I-gel to live cells and confirmed its effect in interfering with the GFP expression. The I-gel shows higher RNAi effect than plasmids in free form or complexed with Lipofectamine. This nanoscale hydrogel, which is able to produce RNA in a cell, provides a platform technology for efficient RNAi system. Interfering RNA have a range of therapeutic and research based applications, issues with delivery have made systems that make siRNAin situ of interest. Here, the author report on the creation of a DNA hydrogel with improved stability and transcription efficiency over plasmid DNA.